Invasive fungal sinusitis: A case report (Indian Journal of Case Reports, 2020)
Fungal sinusitis is the mucosal inflammation of paranasal sinuses (PNSs) due to fungus etiology. The entity remained underdiagnosed earlier because of the non-existence and non-availability of imaging modalities. There is a wide range of clinical symptomatology. Fungal sinusitis requires precise evaluation and decision in type and diagnosis for the correct and appropriate management by an otorhinolaryngologist. The reason for this is being unique radiological features in fungal sinusitis in computerized tomography (CT) and magnetic resonance (MRI). We present the case of a 16-year-old boy who presented with a chronic history of nasal blockage and running nose of 3 months duration and now with fever and headache for the past 2 weeks. He underwent plain X-ray, NCCT, and MRI of PNS. He was diagnosed as having invasive fungal sinusitis on the basis of clinical and classical CT findings supplemented with MRI. He had further been advised surgical contemplation for the total cure as medical management is not the answer. Radiological modalities can precisely differentiate the different subtypes of fungal sinusitis. Otorhinolaryngologists make the management decision and precision on the type of fungal sinusitis keeping in view of involving the neighboring structures.